Adaptive Buenos Aires. Architecture between diversity and demand of modernity - Francesco Casalbordino (Agathón)
In the 21st century, the processes linked to globalization bring significant changes to the way humans inhabit places influencing architectural design. The following essay presents the city of Buenos Aires as an example of Resilience towards cultural diversity and the demand for modernity proper to a global city. Three particular architectural phenomena can be identified – the rascacielo, the villa miseria and the chorizo house – architectures and spaces of the city capable of responding, more or less positively, to the changes brought by the new condition of global culture.